Accelerated Angiogenesis of Human Umbilical Vein Endothelial Cells Under Negative Pressure Was Associated With the Regulation of Gene Expression Involved in the Proliferation and Migration. Issue 6 (17th December 2022) - Fukui, Michika; Matsuoka, Yuki; Taketani, Shigeru; Higasa, Koichiro; Hihara, Masakatsu; Kuro, Atsuyuki; Kakudo, Natsuko
Abstract: Negative pressure has been used as a preferred therapy for wound healing; however, the mechanisms by which negative pressure promotes tissue restoration remain unclear. In the present study, RNA-sequencing analysis was performed to identify differentially expressed genes in human umbilical vein endothelial cells (HUVECs) exposed to negative pressure. Cell viability and DNA synthesis were examined using the cell counting kit-8 assay and bromodeoxyuridine incorporation, respectively. Cell migration was assessed using tube formation, Transwell, and wound healing assays. Activity of the serine/threonine kinase (AKT) signaling pathway was also examined by measuring the levels of phospho-paxicillin, phospho-focal adhesion kinase (p-FAK), and p-AKT1. The exposure of HUVECs to negative pressure enhanced cell proliferation and DNA synthesis. Negative pressure enhanced the migration and invasion of HUVECs, which was accompanied by upregulation of genes involved in angiogenesis, extracellular matrix organization, and cytoskeletal organization. The mRNA levels of growth factors, including placental growth factor and platelet-derived growth factor B, also increased. In addition, phosphorylation of paxicillin, focal adhesion kinase, and AKT increased under negative pressure. Collectively, the findings of this study demonstrated that negative pressure stimulates the angiogenic activity of HUVECs by increasing their proliferation and migration via activation of the AKT signaling pathway.